Spinel-structured high entropy oxide (FeCoNiCrMn)3O4 as anode towards superior lithium storage performance - Wang, Dan; Jiang, Shunda; Duan, Chanqin; Mao, Jing; Dong, Ying; Dong, Kangze; Wang, Zhiyuan; Luo, Shaohua; Liu, Yanguo; Qi, Xiwei (Journal of alloys and compounds, 2020)
High entropy oxide (HEO) is a new-type inorganic material composed of multiple principle metal elements with a single-phase structure and is proved to display many potential unexpected properties such as high structural stability and superionic conductivity. Herein, a novel spinel-structured high entropy oxide (FeCoNiCrMn)3O4 is prepared by high-temperature solid state reaction and evaluated as anode for lithium-ion batteries (LIBs). In-situ high-temperature X-ray diffraction (HT-XRD) is used to reveal structure evolution of mixed oxides with the calcination temperature increase and a single-phase spinel-structured (FeCoNiCrMn)3O4 is obtained at 900 °C. The effect of temperature on structure and electrochemical performance of HEO were investigated, and the HEO-900 anode with commercial mass loading exerts higher capacity (discharge/charge, 1034/680 mAh g−1) and better rate capability (182 mAh g−1 at 2 Ag-1) than HEO-950 and HEO-1000 for its moderate particle size, and all the three samples show excellent cycling stability. Ex-situ XRD and transmission electron microscope are applied to unravel the lithium-storage mechanism of (FeCoNiCrMn)3O4, an amorphization reaction process occurs during the initial discharging and the amorphous structure is maintained in subsequent cycles. The synergetic effect of multiple metal cations with different radius, valence states and reaction potentials and entropy stabilization effect make the HEO display a superior electrochemical performance in LIBs. This work provides a new concept to design multi-element transition metal oxide anode materials by high entropy strategy. [Display omitted] •A spinel-typed high entropy oxide (FeCoNiCrMn)3O4 is prepared by solid state reaction.•In-situ high temperature XRD is used to reveal structure evolution of HEO formation.•The high entropy oxide is explored as an anode material for lithium-ion batteries.•Well-mixed cations make HEO show a excellent cycling stability and rate capability.